Una nueva especie de Ceratophrys (Anura, Leptodactylidae) en el Neógeno de la provincia de Buenos Aires, Argentina (Ameghiniana, 2014)
The new species Ceratophrys ameghinorum is described. This species is distinguished from other species of this genus in the presence of a triangular squamosal otic plate that is projected markedly above the dorsal surface of the skull. The external edge of the otic plate bears a longitudinal crest that ventrally turns into a lateral wall. In lateral view, the length of the otic ramus represents more than 55% of the length of the ventral ramus. The atlas bears a pair of cotyles with discontinuous articular surfaces. The species C. prisca Ameghino is considered species inquirenda.